2021
DOI: 10.1136/bmj.m4903
|View full text |Cite
|
Sign up to set email alerts
|

Use of proton pump inhibitors to treat persistent throat symptoms: multicentre, double blind, randomised, placebo controlled trial

Abstract: Objective To assess the use of proton pump inhibitors (PPIs) to treat persistent throat symptoms. Design Pragmatic, double blind, placebo controlled, randomised trial. Setting Eight ear, nose, and throat outpatient clinics, United Kingdom. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
42
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 31 publications
0
42
0
4
Order By: Relevance
“…34 In addition, PPIs are frequently initiated without a definite indication, notably for empiric treatment of laryngopharyngeal symptoms of cough, throat clearing, globus, and voice hoarseness. Because an RCT has definitively demonstrated that PPIs have no benefit in the empiric management of these symptoms, 35 these patients should be considered for de-prescribing.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…34 In addition, PPIs are frequently initiated without a definite indication, notably for empiric treatment of laryngopharyngeal symptoms of cough, throat clearing, globus, and voice hoarseness. Because an RCT has definitively demonstrated that PPIs have no benefit in the empiric management of these symptoms, 35 these patients should be considered for de-prescribing.…”
mentioning
confidence: 99%
“…In addition, PPIs at any dose are ineffective in managing laryngopharyngeal symptoms. 35 Highdose PPIs are indicated for Zollinger-Ellison syndrome, which is exceedingly rare (1/1,000,000). 43,44 Therefore, most high-dose PPI users should be considered for stepping down to standard dosing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although many studies have focused on laryngopharyngeal reflux (LPR), laryngitis, asthma, and chronic cough, their results are inconsistent and only a few are randomized controlled trials (RCTs). The few RCTs that have recently been published suggest that PPIs have little or no superiority to placebo in the treatment of extraesophageal GERD symptoms [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our group recently undertook a rigorous randomised controlled trial (RCT) investigating the role of PPIs in persistent throat symptoms. 6 During our literature reviews, we became concerned about the poor standard of publications, particularly in the systematic review literature. We therefore aimed to critically appraise the literature to determine their scientific validity.…”
mentioning
confidence: 99%